Prognostic Value of Cardiac Axis Deviation in Systemic Sclerosis–Related Pulmonary Hypertension. Issue 7 (5th April 2022) - Lui, Justin K.; Sangani, Ruchika A.; Chen, Clara A.; Bujor, Andreea M.; Trojanowski, Marcin A.; Gopal, Deepa M.; LaValley, Michael P.; Soylemez Wiener, Renda; Klings, Elizabeth S.
Abstract : Objective: Systemic sclerosis–related pulmonary hypertension (SSc‐PH) is a common complication of SSc associated with accelerated mortality. The present study was undertaken to investigate whether cardiac axis deviation indicates abnormalities in cardiac function allowing for prognostication of disease severity and mortality. Methods: This was a retrospective study in which electrocardiograms (ECGs) were reviewed for cardiac axis deviation and their association with echocardiography and cardiopulmonary hemodynamics on right‐sided heart catheterization. The primary outcome observed was all‐cause mortality from the time of PH diagnosis. Results: ECG results were reviewed from 169 patients with SSc‐PH. Right axis deviation (RAD) and left axis deviation (LAD) occurred in 28.4% and 30.8% of patients with SSc‐PH, respectively. Compared to those without RAD, patients with RAD exhibited predominantly right‐sided cardiac disease on echocardiography and increased PH severity by cardiopulmonary hemodynamics including a greater mean ± SD pulmonary artery pressure (42.0 ± 12.5 mm Hg versus 29.8 ± 7.0 mm Hg) and mean ± SD pulmonary vascular resistance (645.6 ± 443.2 dynes · seconds/cm 5 versus 286.3 ± 167.7 dynes · seconds/cm 5 ). LAD was associated with predominantly left‐sided cardiac disease on echocardiography but was not associated with PH severity on cardiopulmonary hemodynamics. Both RAD (hazard ratio 10.36 [95% confidence interval 4.90–21.93], P < 0.001) and LAD (hazard ratio 2.94 [95% confidence interval 1.53–5.68], P = 0.001) were associated with an increased hazard for all‐cause mortality. Conclusion: RAD and LAD reflect structural cardiac abnormalities and are associated with poor prognosis in patients with SSc‐PH. These findings support the importance of electrocardiography, an inexpensive, widely available noninvasive test, in risk stratification.